Acute and Hyper-acute Thoracolumbar Corpectomy for Traumatic Burst Fractures Using a Mini-open Lateral Approach. Issue 2 (15th January 2018) - Smith, William D.; Ghazarian, Nick; Christian, Ginger
Abstract : Study Design: Retrospective chart review. Objective: The purpose of this study was to examine the feasibility of acute (<24 hours) and hyperacute (<8 hours) treatment of thoracolumbar burst fractures to maintain or improve spinal injury scores. Summary of Background Data: Historically, treatment of spinal burst fractures within 24 hours from injury was considered an "acute" treatment timeframe. Patient polytrauma triage, multiple surgical specialty, and hospital resource coordination affect time to treatment. The mini-open lateral approach for thoracolumbar corpectomy obviates the need for an approach surgeon, which may allow for early surgical intervention. Methods: Sixteen patients treated within 24 hours with a mini-open lateral corpectomy for traumatic spinal pathology were reviewed for preoperative, perioperative, and postoperative data. Neurologic status was assessed using American Spinal Injury Association (ASIA) scores. Fractures occurred primarily from L1 to L3. Wide-footprint expandable titanium devices were used in 75% of patients. All patients received supplemental fixation. Results: Average time from injury to admission to the hospital (emergency room [ER]) was 1.8 hours, with an average time from the ER to operating room (OR) of 8.2 hours and an average OR time of 2.7 hours. Eight patients required ⩽8 hours from injury event to surgical initiation, whereas seven patients required between 8 and 24 hours for surgery initiation (one patient with incomplete surgical timing record). Blood loss averaged 646 mL without intraoperative complication. One perioperative complication occurred and one patient developed an asymptomatic inferior vertebral body fracture. Length of hospital stay averaged 6 days. At last follow-up, nearly all patients experienced full or near-complete neurologic recovery with at least one ASIA grade improvement seen in 73% and 20% of patients improving two grades or more. Conclusion: These results suggest that mini-open lateral approaches allow immediate decompression through hyperacute (<8 hours) treatment of spinal burst fractures in eligible patients. Additionally, low perioperative and postoperative morbidity allows for hastened recovery. Level of Evidence: 4